Effect of substrate type on diatom-based water quality assessments in the Mount Lofty Ranges, South Australia - Jenny Richards; John Tibby; Cameron Barr; Peter Goonan (Hydrobiologia, 2020)
Diatoms have been widely used in stream health assessments as they are highly sensitive to water quality. There is no standardised method for diatom-based stream health assessments causing many substrates, both natural and artificial, to be used. Few studies have investigated the impact of substrate type on diatom assemblages in streams with highly variable water levels. To determine if the substrate type affects these assessments, diatoms were analysed from an artificial substrate (rope), rock and mud, from 17 sites in the Mount Lofty Ranges, South Australia. Rope has been advocated as a substrate as it mimics aquatic plants, while having advantages of artificial substrates (e.g. standardised habitat). We found that substrate type did not affect the stream health assessment based on the Diatom Species Index for Australian Rivers and hence the additional cost of deploying ropes in such studies is unlikely to be warranted. However, substrate type influenced diatom–nutrient relationships, with no relationship between nutrients in the stream water and diatoms in the mud substrate—possibly due to the nutrient subsidy provided by mud. Therefore, by contrast, the absence of nutrients provided by the rope substrate indicates it is suited to studies of nutrient status and sensitivity in streams.